Application Of Contextual Methods To Improve Short Writing Ability For Class Ix Students Of Junior High School - Sembiring, Anggi Shavira (Cattleya Darmaya Fortuna, 2022)
Writing is an activity to express thoughts, ideas or opinions and solve problems through written language media. Short stories are works of fiction that are fictitious, narrative or short storytelling (the storyline is solid while the background and flashbacks are included in passing). Because of its short form, short stories demand a concise narrative, not specific details that are